1991
DOI: 10.1159/000293095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-Term Effects of Estrogen and Clomiphene Citrate on Pituitary and Uterine Function in Ovariectomized Rats

Abstract: The effects of estradiol-17Β (E2) and clomiphene citrate (CC) on pituitary-uterine function in ovariectomized (OVX) rats were compared in two experiments. In experiment 1 CC completely blocked E2 stimulation of uterine weight when administered concurrently for 10 and 30 days. In experiment 2, content of total (occupied and unoccupied) uterine nuclear estrogen receptors was increased by E2, but not by CC, compared to OVX controls. Only a fraction of the nuclear receptors was occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, a study in ovariectomized rats treated with clomiphene for 30 days showed no changes in serum PRL levels. 15 Similarly, when clomiphene was given to subfertile men at the dose of 50 mg/day for 3 months, basal PRL levels remained unchanged. 19 In the present study, serum PRL levels did not change even after the addition of E2 to the clomiphene or raloxifene regimen.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, a study in ovariectomized rats treated with clomiphene for 30 days showed no changes in serum PRL levels. 15 Similarly, when clomiphene was given to subfertile men at the dose of 50 mg/day for 3 months, basal PRL levels remained unchanged. 19 In the present study, serum PRL levels did not change even after the addition of E2 to the clomiphene or raloxifene regimen.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding clomiphene, the literature lacks data on the effect of this compound on PRL secretion in postmenopausal women. However, a study in ovariectomized rats treated with clomiphene for 30 days showed no changes in serum PRL levels 15 . Similarly, when clomiphene was given to subfertile men at the dose of 50 mg/day for 3 months, basal PRL levels remained unchanged 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations